Forestland allocation and livelihood assets of the poor households in upland area of Vietnam : a case study at Thuong Nhat Commune, Nam Dong District, Thua Thien Hue Province - Le Van Lan; Jourdain, Damien; Shrestha, Rajendra Prasad; Shivakoti, Ganesh P.; HUA; AIT Fellowship; Ford Foundation; HUAF (Pathum Thani : Asian Institute of Technology, 2012)
First of all, my sincere gratitude goes to Prof. Ga nesh P. Shivakoti, my supervisor, who has given me valuable direction, academic advice, c riticism and encouragement through building and writing up this thesis. Without his pr ofessional guidance and support, my thesis would not be possible and completed. I would like to express my sincere thanks to Dr. Ra jendra Shrestha and Dr. Damien Jourdain who have given me not only helpful comment s but also important suggestions to look at both the research proposal and the thesis. I am greatly indebted to all of my professors and d octors who have given me knowledge, practice and kindness during the Master course. I a lso would like to send my thanks to all of my classmates for their sharing, comment and ass istance during the course. In carrying out the field works, I received honest assistance from my colleagues in the Centre for Rural Development in Central Vietnam (CR D) and Hue University of Agriculture and Forestry (HUAF). On this occasion, I would like to thank all of them for their help through relevant discussions and debatem ents. My thanks also go to all households and other peopl e, staffs that participated in my data collection in Thuong Nhat commune and Nam Dong dist rict. This research would have been not possible without their willingness and con tribution. I would like in particular to express my love to my wife who is always my consolation and encouragement whenever I am down. Last but not leas t, my family is immensely meaningful to my work and my study. My gratitude go es to my parents, my brothers and sisters, my children who encouraged me so much to c omplete the thesis.
A thesis submitted in partial fulfillment of the re quirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2012
Keywords: Forests and forestry -- Vietnam -- Thua Thien Hue; Households -- Vietnam -- Thua Thien Hue; Home economics -- Vietnam -- Thua Thien Hue